The Application of Chiral Resorcinarenes as Modifiers of Crystallization and Inhibitors of Corrosion - Bertata, Munna Ali Mohamed (Curtin University, 2018)
Crystallization and corrosion processes are important in industry so, variety of organic additives have been used to modify crystallization or inhibit corrosion. In this project, macrocyclic compounds coupled with amino acids have been synthesised and investigated to determine their influence on the crystallization of calcium carbonate, barium sulfate and calcium oxalate and on inhibition of carbon steel corrosion. The results showed that the smaller compounds had the greater impact.